RedeCI: Collaboration and Scientific Production in Information Science in Brazil (Perspectivas em Ciência da Informação, 2007)
This paper presents the methodology and some preliminary results of a coauthorship network, obtained through the use of a technique knows likesocial network analysis - SNA - , in Brazilian Information Science as part of an ambitious project called RedeCI. The numbers of authors per paper arerelatively reduced and the numbers of papers with a single author are relevant. The number of authors with a single publication shows results consistent withthe literature about scientific productivity, measured by number of papers authored, following Lotka’s law. The centrality measures estimated using the social network analysis - SNA - are poorly correlated.